ASEAN's norm adherence and its unintended consequences in HADR and SAR operations. Issue 4 (7th August 2016) - Loh, Dylan Ming Hui
Abstract: This paper examines the effects and expressions of norm compliance in Association of Southeast Asian Nations (ASEAN) and the 'unintended consequences' arising from such compliance. This is done through an analysis of ASEAN's responses in humanitarian assistance and disaster relief (HADR) efforts in the Typhoon Haiyan disaster and in the search for missing flight MH370. It argues that the lethargic ASEAN responses in the Haiyan disaster and the uncoordinated search efforts for missing flight MH370 are unintended outcomes arising from norm adherence specifically to the norms of 'respect for sovereignty' and 'consensual decision-making' which constrained the range of ASEAN responses.